Bride Price Payment and Justification of Sexual Violence Among Women in Ghana*These authors contributed equally to this work. - Kojo Oduro, Joseph (Journal of interpersonal violence, 2022)
Although insights on bride price and domestic violence have been explored in Ghana, very little is known about payment of bride price and the justification of sexual violence. We investigated the payment of bride price and justification of sexual violence among women (N = 4,222) in Ghana, dwelling on the 2014 Ghana Demographic and Health Survey. Two binary logistic regression models were fitted. We adjusted for significant sociodemographic variables. The findings revealed that women whose partners had paid their bride price had higher odds [OR = 1.54; CI = 1.174, 2.00] of justifying sexual violence, compared to those whose partners had not paid. We found that women with primary [AOR = 0.55; CI = 0.44?0.71] and secondary/higher [AOR = 0.47; CI = 0.36?0.60] levels of education had lower odds of accepting sexual violence. Women in the rich wealth quintile [AOR = 0.32; CI = 0.22, 0.46] had lower odds of justifying sexual violence. Our study has illustrated the need for women to appreciate that payment of bride price does not imply that their fundamental human rights have been bought by men, but they rather become partners. This information can form part of premarriage counselling and human rights initiatives by the Ministry of Gender and Social Protection. That is, the content of marriage counselling may be expanded to include issues on IPV, its implications, and legal consequences. Such information can develop personal realization and urge women to report any violent advances to the police and appropriate authorities for the required legal action to be taken. This may deter others to desist from violence perpetration against women. At the community level, chiefs and other leaders of high repute can be made anti-IPV ambassadors. The Ministry of Health and other nongovernmental anti-violence organizations can also collaborate to strengthen education on anti-sexual violence programs by using the mass media.